The management of multidrug-resistant Enterobacteriaceae. Issue 6 (December 2016) - Bassetti, Matteo; Peghin, Maddalena; Pecori, Davide
Abstract : Purpose of review: Multidrug-resistant (MDR) Enterobacteriaceae are often related to the production of extended-spectrum b-lactamases (ESBLs) and carbapenemase-producing Enterobacteriaceae (CRE), and represent an increasing global threat. Recommendations for the therapeutic management of MDR-related infections, however, are mainly derived from retrospective and nonrandomized prospective studies. The aim of this review is to discuss the challenges in the treatment of patients with infections because of MDR Enterobacteriaceae and provide an expert opinion while awaiting for more definitive data. Recent findings: To avoid the selection of carbapenemase-producing Enterobacteriaceae, carbapenem-sparing strategies should be considered. B-lactams/b-lactamase inhibitors, mainly piperacillin–tazobactam, minimum inhibitory concentration (MIC) 16/4mg/ml or less represents the best alternative to carbapenems for the treatment of ESBL-producing strains. Overall, combination therapy may be preferred over monotherapy for CRE. The combination of a carbapenem-containing regimen with colistin or high-dose tigecycline or aminoglycoside can be administered at high-dose prolonged infusion with therapeutic drug monitoring for the treatment of CRE with MIC for meropenem 8–16 mg/l or less. For MIC higher than 8–16 mg/l, the use of meropenem should be avoided and various combination therapies based on the in-vitro susceptibility of antimicrobials (e.g., colistin, high-dose tigecycline, fosfomycin, and aminoglycosides) should be selected. Summary: Carbapenem-sparing strategies should be used, when feasible, for ESBL infections. The majority of available nonrandomized studies highlight that combination for CRE seem to offer some therapeutic advantage over monotherapy. Strict infection control measures toward MDR Gram-negative pathogens remain necessary while awaiting for new treatment options.